1989
DOI: 10.1159/000261200
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Streptococcussobrinus Induced by Xylitol, NaF and ZnCl2

Abstract: The effect of xylitol, NaF, or ZnCl2 on the ultrastructure of Streptococcus sobrinus OMZ 176 was studied. The bacteria were grown statically in air for 8 h in brain-heart infusion broth supplemented with 33 mM Xylitol, 2.5 mM NaF, 0.5 mM ZnCl2, separately or in combination. The bacteria were washed briefly and prepared for scanning and transmission electron microscopy. All three agents and their combinations induced distinct ultrastructural alterations. The alterations were related to var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…In vitro, xylitol modifies the synthesis of polysac charides from sucrose in Streptococcus mutans, thereby decreasing the ability of the cells to adhere to hard surfaces [Verran and Drucker, 1982;Soderling et al, 1987], In vitro studies also suggested that xylitol could cause ultrastructural changes in streptococci [Tuompo et al, 1983;Scheie et al, 1989], which in turn could affect the adhesion properties of the orga nism. The present study, however, did not reveal any differences between the habitual xylitol consumers and the controls in those properties that determine the adhesion of salivary mutans streptococci to plastic strips.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, xylitol modifies the synthesis of polysac charides from sucrose in Streptococcus mutans, thereby decreasing the ability of the cells to adhere to hard surfaces [Verran and Drucker, 1982;Soderling et al, 1987], In vitro studies also suggested that xylitol could cause ultrastructural changes in streptococci [Tuompo et al, 1983;Scheie et al, 1989], which in turn could affect the adhesion properties of the orga nism. The present study, however, did not reveal any differences between the habitual xylitol consumers and the controls in those properties that determine the adhesion of salivary mutans streptococci to plastic strips.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies of S. mutuns and S. sobrinus have shown that the presence of xylitol in the incubation medium results in cell degradation and autolysis, intracellular vacuoles, lamellated formations in the cytoplasmic membrane (38) and in other ultrastructral alterations (39). This presumably constitutes further evidence of a bacteriostatic effect of xylitol on mutans streptococci.…”
Section: Metabolism By Oral Microorganismsmentioning
confidence: 98%
“…Stannous fluoride and amine fluoride as well as numerous metallic ions have demonstrated antimicrobial effectiveness. 32,33 Tin, zinc, copper and others have demonstrated anti-microbial effects, but none have demonstrated anti-caries effectiveness. Essential oils, a mixture of thymol, eucalyptol, methyl salicylate and menthol have been demonstrated to be effective in preventing the build-up of supra-gingival plaque and gingivitis, 34,35 but have not demonstrated effectiveness in the reduction of caries lesions.…”
Section: Anti-microbial Therapiesmentioning
confidence: 99%